Diversity and bioactivity of endophytic fungi isolated from various fruit organs of Physalis angulata - BUDI EKO WAHYUDI; ELFITA ELFITA; HARY WIDJAJANTI; SALNI SALNI; ELIZA ELIZA; JULINAR JULINAR; EVA MUSIFA (Biodiversitas Journal of Biological Diversity, 2025)
Abstract. Wahyudi BE, Elfita, Widjajanti H, Salni, Eliza, Julinar, Musifa E. 2025. Diversity and bioactivity of endophytic fungi isolated from various fruit organs of Physalis angulata. Biodiversitas 26: 1485-1499. Physalis angulata plant is known by Indonesian people for its efficacy as a traditional medicine. The fruit is traditionally known as antidiabetic, anti-inflammatory and antibacterial. The efficacy of this fruit can also be obtained through its endophytic fungi isolated from parts organ of namely peduncle, calyx and pericarp all these aspects. The objective of this study was to isolate endophytic fungi from different organs of P. angulata fruit, namely peduncle, calyx and pericarp and determine the diversity, bioactivity and phytochemical content while comparing all aspects with the host. Endophytic fungi were isolated from peduncle, calyx and pericarp using sterile Potato Dextrose Agar (PDA) media. The fungi were cultured on Potato Dextrose Broth (PDB) for 4 weeks, then partitioned in ethyl acetate and evaporated using rotary evaporator. The host plant organs were macerated in methanol solvent and evaporated. The antioxidant activity was tested by the 1,1-diphenyl-2-picrylhydrazyl (DPPH) method, while the antibacterial activity tested by the Kirby-Bauer diffusion method. Potential compounds were analyzed using Thin Layer Chromatography (TLC), then Liquid Chromatography Mass Spectrometry/Mass Spectrometry (LC-MS/MS) was used to determine the compounds contained in the extract. The results showed that a total of 18 fungal isolates were obtained from the plant, including 5 isolates from the peduncle (CT1-CT5), 7 isolates from the calyx (EP1-EP7), and 6 isolates from the pericarp (BP1-BP6) which were belonged to 11 genera. Aspergillus was the dominant fungus as it was obtained from the peduncle, calyx and pericarp. The overall bioactivity of endophytic fungi was better than its host. Antibacterial and antioxidant activities were not comparable, some extracts had weak antibacterial but strong antioxidants. Isolate CT5-(Diaporthe sp.) was selected for LC-MS/MS analysis because it showed very strong activity. The results of present research provide information that endophytic fungi of P. angulata fruit have great potential to support medical development in the discovery of new therapeutic agents from nature.